Design and evaluation of a stearylated multicomponent peptide-siRNA nanocomplex for efficient cellular siRNA delivery. (February 2017) - Wan, Yu; Moyle, Peter M; Gn, Pei Z; Toth, Istvan
Aim: To develop a new synthetic peptide-based nanoparticulate siRNA delivery system.Materials & methods: DEN-K(GALA)-TAT-K(STR) was generated by incorporating stearic acid into a multicomponent peptide (DEN-K(GALA)-TAT), containing a cationic poly-L-lysine dendron, an endosome-disrupting peptide GALA and a cell-penetrating peptide TAT(48–60). Its physicochemical characteristics, size, toxicity, cellular uptake and gene knockdown activity of the peptide/siRNA complexes were studied.Results: DEN-K(GALA)-TAT-K(STR) exhibited a pH-responsive behavior, which assists with endosomal escape. When siRNA was delivered by DEN-K(GALA)-TAT-K(STR), it showed a significantly enhanced cellular uptake, compared with the nonlipidic peptide. This system also displayed enhanced knockdown efficiency and reduced cytotoxicity over the widely used delivery system branched 25-kDa polyethyleneimine.Conclusion: Our stearylated multicomponent delivery system has great potential as an efficient siRNA delivery vector.